2002
DOI: 10.1046/j.1439-0388.2002.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibre structure and metabolites in M. longissimus dorsi of Wild Boar, Pietrain and Meishan pigs as well as their crossbred generations

Abstract: Fibre traits and glycolytic metabolites in musculus longissimus dorsi of European Wild Boar, Pietrain and Meishan as well as their F1 and F2 crossbred generations were evaluated and compared. Pietrain had the highest relative number of white fibres and the largest muscle fibres. Wild Boar showed the smallest muscle fibres. The R‐value and lactate level of Wild Boar and Meishan were low, whereas Pietrain had high R‐values and lactate levels. The glycogen level was highest in Wild Boar and lowest in Meishan. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
15
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 14 publications
5
15
1
Order By: Relevance
“…Similarly as Bogucka et al (2008), we observed a significantly higher proportion of type I myofibers in 3-week, 7-month and 2-year-old WP than in DP. This is in contradiction with the findings of other studies, in which no differences in the proportion of type I myofibers were detected (Losel et al, 2013) or type I myofibers were even more numerous in the longissimus dorsi muscle of DP than of WP (Muller et al, 2002;Rehfeldt et al, 2008). The detection of type I myofibers is reliable, regardless of whether immunohistochemistry or myosin ATPase-based methods are used.…”
contrasting
confidence: 95%
See 2 more Smart Citations
“…Similarly as Bogucka et al (2008), we observed a significantly higher proportion of type I myofibers in 3-week, 7-month and 2-year-old WP than in DP. This is in contradiction with the findings of other studies, in which no differences in the proportion of type I myofibers were detected (Losel et al, 2013) or type I myofibers were even more numerous in the longissimus dorsi muscle of DP than of WP (Muller et al, 2002;Rehfeldt et al, 2008). The detection of type I myofibers is reliable, regardless of whether immunohistochemistry or myosin ATPase-based methods are used.…”
contrasting
confidence: 95%
“…In general, these studies revealed that domestication and breeding selection are associated with myofiber hypertrophy and changes in fibre type composition with a prevalent age-dependent increase in the proportion of fast glycolytic myofibers (Szentkuti and Schlegel, 1985;Weiler et al, 1995;Muller et al, 2002;Ruusunen and Puolanne, 2004). Most of these studies were based on the myosin ATPase reaction and metabolic enzyme histochemistry with a simplified myofiber type classification scheme (slow-twitch oxidative, fast-twitch oxidative, fast-twitch glycolitic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Bonneau et al (1990) obtained higher oxidative (CS and HAD) and lower glycolytic (LDH) enzyme activities in L muscle from purebred Meishan compared to that of adult LW pigs. In comparison with Pietrain pigs, but also with wild boars, Müller et al (2002) also found a lower glycogen content and a higher percentage of red fibres in L muscle of purebred Meishan. In a recent study, Lefaucheur et al (2004) confirmed that L muscle from Meishan pigs is less glycolytic and more oxidative than that from LW.…”
Section: Muscle Fibre Traitsmentioning
confidence: 64%
“…In comparing wild boar (as a wild ancestor), Meishan (commercial breed unselected for muscling), Pietrain (commercial breed selected for muscling) and their crossbred generations, Müller et al (2002) indicated that crossbreds often had muscle fibre histochemistry between those of the founder breeds.…”
mentioning
confidence: 99%